A 2.5 year study on health and locomotion symmetry in young Standardbred horses subjected to two levels of high intensity training distance. (January 2016) - Ringmark, S.; Jansson, A.; Lindholm, A.; Hedenström, U.; Roepstorff, L.
Highlights: Health in Standardbred horses was subjected to a reduced training program. By reducing the high intensity training distance the number of days lost to training was reduced. Introduction of new training may cause alterations in locomotion symmetry. Objective locomotion analysis is recommended in young horses during the training phase. Abstract: The aim of this study was to document effects of two high-intensity training regimes on horse health. Sixteen Standardbred horses in training from September as 1-year-olds with the goal to race as 3-year-olds were used in a 2.5 year study. Horses were trained in either a control training program (C-group) or in a program with 30% reduced high intensity distance compared to the C-group (R-group). Clinical examinations were performed nine times. Locomotion asymmetry was registered with a sensor-based system 17 times. There was no difference in health scores, locomotion asymmetry or veterinary treatments between groups. Subjective lameness score and objective front limb locomotion asymmetry increased during the spring both as 2- and 3-year-olds after introduction of speed- and uphill interval training but decreased during winter. Hind limb locomotion asymmetry increased during spring as 2-year-olds and was still above initial level in December as 3-year-olds. Horses that qualified for races early had less asymmetric front limb locomotion and were less lame in clinical examinations (0.7 ± 0.3 vs. 1.6 ± 0.2 degrees [AAEP scale], P = 0.04) than late qualifiers. Days lost to training were higher in C-group than in R-group (27 ± 3% and 17 ± 3%, P = 0.029). It is concluded that (1) less days may be lost to training by reducing the high intensity training distance and (2) the introduction of new training may alter locomotion asymmetry and this can be detected with objective locomotion analysis.